The Inclusion of the Migrant Children in the Education System of the Republic of Serbia – A Human Rights Lesson - Dakić, Milan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The process of enabling the children – regardless of their legal status or objective circumstances – to fulfil the right to education under the same or similar conditions, is being precisely tested in the uncertain times, as is the European migrant crisis that began in 2015. As already proven by numerous instances, the universal value of education justifies its quality as a fundamental human right even in the short term. Education serves the best interests of children, as the most important tool of their inclusion in the society, their window into a better world, as well as a functional therapy in overcoming the traumas which, unfortunately, take place as results of the horrors of war, poverty and concomitant hardships as the primary causes of their forced migration into our country. Consequently, education must not be treated as a less important necessity, which is often the case in situations that require urgent aid to large numbers of people. The implementation of adequate education programs should immediately follow or, ideally, go apace with the provision of the most basic needs: shelter, food (including water), clothing and urgent medical care. The range of duties of the Republic of Serbia to provide such aid to migrants – and the migrant children in particular – is defined through the international agreements signed by our country. Furthermore, it is a part of an effort to advance our country’s human rights commitment within the global community. Most importantly, there is a positive influence that the inclusion of the migrant children would effectuate in regard to our children and their personal development. Therefore, as the country’s unofficial “representatives” and sincere hosts, the children of Serbia would demonstrate empathy and solidarity. Accordingly, these utmost human values would be learned and developed through direct communication, instead of solely by the agency of educational institutions.